Ethnic Variations in Spirometric Parameters A Comparative Study - M. Shindhe, Varsha; A. Balikai, Fareedabanu; Magadum, Amit; M. Benni, Jyoti; Ambiger, Sudha; M. Shindhe, Maheshkumar (Journal of Neonatal Surgery, 2025)
Objective: High-altitude adaptation is a multifaceted process involving various physiological adjustments. Tibetans, having inhabited high-altitude regions for centuries, have developed distinctive physiological adaptations to thrive in hypoxic environments. This study aimed to investigate whether Tibetans exhibit superior lung function adaptations compared to the Indian population, and whether these adaptations are innate, enabling them to excel in high-altitude environments. Material and Methods: A comparative analysis was performed on 100 male youths, comprising 50 Tibetans and 50 Indians, carefully matched for age, sex, and anthropometric characteristics. Utilizing the Spiroanalyser SPL 95, a comprehensive assessment of lung function was conducted, encompassing vital capacity (VC), expiratory reserve volume (ERV), inspiratory reserve volume (IRV), inspiratory capacity (IC), and tidal volume (TV). Results: Tibetan youths demonstrated significantly superior lung function, with notably higher values for vital capacity (VC), expiratory reserve volume (ERV), inspiratory reserve volume (IRV), inspiratory capacity (IC), and tidal volume (TV), compared to their Indian counterparts. Conclusion: The marked differences in lung function parameters observed in this study indicate that Tibetans possess unique physiological adaptations, likely rooted in genetic factors, which confer enhanced lung function capabilities. These adaptations enable Tibetans to excel in high-altitude environments, underscoring their remarkable ability to thrive in hypoxic conditions.